Morphologic Reproducibility, Genotyping, and Immunohistochemical Profiling Do Not Support a Category of Seromucinous Carcinoma of the Ovary. (May 2017) - Rambau, Peter F.; McIntyre, John B.; Taylor, Jennifer; Lee, Sandra; Ogilvie, Travis; Sienko, Anna; Morris, Don; Duggan, Máire A.; McCluggage, W. Glenn; Köbel, Martin
Abstract : The 2014 World Health Organization Classification of Tumors of Female Reproductive Organs endorsed the new category of seromucinous carcinoma, a neoplasm that exhibits morphologic and immunophenotypic overlap with other histotypes of ovarian carcinoma. The goal of this study was to determine whether seromucinous carcinoma was a distinct histotype by assessing its diagnostic reproducibility and comparing its molecular composition to the 5 major histotypes of ovarian carcinoma. Thirty-two tumors diagnosed as seromucinous carcinomas from 2 centers were studied. Eighteen cases were randomly selected for a review set comprising a total of 50 ovarian carcinomas of various histotypes. Morphologic histotype was independently assessed by 4 pathologists. For the 32 seromucinous carcinomas, a histotype-specific immunophenotype was assigned using a diagnostic immunohistochemical panel. Histotype-specific genotype was assigned using a combination of immunohistochemistry and targeted next-generation sequencing for somatic mutations, including genes recurrently mutated in ovarian carcinomas. There was low to modest agreement between pathologists with the reference diagnosis of seromucinous carcinoma, ranging from 39% to 56% for the 4 observers. The immunophenotype was not unique but overlapped predominantly with endometrioid and to a lesser extent with mucinous and low-grade serous carcinoma. Genomic and immunohistochemical alterations were detected in a number of target genes, including KRAS (70%), PIK3CA (37%), PTEN (19%), and ARID1A (16%); no CTNNB1 mutations were identified. Nine cases (30%) harbored concurrent KRAS/PIK3CA mutations. An endometrioid genotype was assigned to 19 cases, a low-grade serous genotype to 9, and a mucinous genotype to 1 and 3 cases were uninformative. Integrating morphology, immunophenotype, and genotyping resulted in reclassifying the seromucinous carcinomas to endometrioid 23/32 (72%), low-grade serous 8/32 (25%), and mucinous 1/32 (3%). The morphologic diagnosis of seromucinous carcinomas is not very reliable and it does not exhibit a distinct immunophenotype or genotype. The molecular features overlap mostly with endometrioid and low-grade serous carcinomas. Our data suggest the category of seromucinous carcinoma be discontinued as ancillary molecular tests can assign cases to one of the major histotypes. Abstract : Supplemental Digital Content is available in the text.